Papers - - Production - Foreign - Petroleum Prospecting Operations in Australia and New Guinea during 1935 - W. G. Woolnough (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1936)
There has been no noteworthy increase in production during 1935; but, on the other hand, there have been ample manifestations of a considerable increase in interest and activity in connection with petroleum prospecting. The Lakes Entrance field, in the State of Victoria, on the coast some 120 miles east of Melbourne, remains the only actual producer; and this production, consisting of lubricating stock devoid of light fractions, is very small in amount. Arrangements have been completed under which a series of "scout bores" for structure testing in the region of Lakes Entrance will be sunk by the Government of the State of Victoria, assisted by a subsidy from the Federal Government. Prospecting In the State of New South Wales, brilliant geological research in very difficult country, carried out by geologists of Oil Search Ltd., has revealed several previously unsuspected domal structures in the Sydney-Newcastle coal basin. These have been mapped in detail, and a test well is being sunk at Kulnura, 10 miles west of Wyong and 40 miles north of Sydney. At the date of writing this well has reached a depth of 1250 ft., 10-in. casing having been set at 1248 feet. Superficial formations consist of the Hawkesbury sandstone and Narrabeen beds of the Hawkes-bury system (fresh-water Triassic). It is anticipated that the upper coal measures of the Kamilaroi (Permo-Carboniferous) will be entered almost immediately. The objectives of the drilling are the upper and lower marine beds of the Kamilaroi system, which are regarded as promising as potential source—and reservoir—beds for oil. At Mulgoa, 30 miles west of Sydney, a bore is being sunk by the same company, Oil Search Ltd., to test for natural gas on a well defined structure located by the company's geologists. Noteworthy flows of gas have been encountered, but nothing approaching a commercial supply has been struck. It is considered probable that the gas has been derived